Pengaruh Kualitas Pelayanan Terhadap Loyalitas Nasabah Debitur Pada PT. Bank BTPN Purna Bakti Cabang Jambi - Osrita Hapsara; Susilawati .; Akhmad Irwansyah Siregar (Sekolah Tinggi Ilmu Ekonomi STEMBI Bandung, 2017)
The average the development of the total credit recipients pension to PT. Bank BTPN Purna Bakti the branch jambi in the past five years of 2.60 % The average number of loans in PT. Bank BTPN Purna Bakti the branch Jambi in the past five years of 11,95 % .This fact shows that there are indications quality drop services to the year. Dimension for measuring quality of services is reliability, responsibility, competence, acces, courtesy, communication, credulity, security, understanding and tangibles.While dimension for measuring loyalty repeat the purchase, retention and referalls. The calculation on SPSS 20 get the regression equation is Y = 1,916 + 0,470 X. From the testing determination and obtained value r2 in table 4.10 of 0,279 this igure stated that variable x or the quality of services able to explain the variable y or loyalty debtors of 27,90 % otherwise 72,100 % caused by other variables outside variable the treatment . A correlation coeficient between the quality of service for loyalty debtors to PT. Bank BTPN Purna Bakti the branch Jambi is 0,528 , it means there are enough closely relations between variables x or quality of service and y or loyalty debtors to PT. Bank BTPN Purna Bakti the branch Jambi Value t count on the variables of the quality of services is of 5,963 & gt; t table 1,9861 with a significantly by 0,000 & it; probability significant α = 0.05, so ho were rejected and h1 accepted.This means that there are significant impact between quality service for loyalty debitors. Kata Kunci : Service quality, Customer loyality.